Unable to Conform, Unwilling to Rebel? Youth, Culture, and Motivation in Globalizing Japan - Toivonen, Tuukka; Norasakkunkit, Vinai; Uchida, Yukiko (Frontiers in Psychology, 2011)
This paper investigates the effects of globalization on Japanese young adults from sociological and psychological perspectives. While Japan’s socio-economic institutions have shown mainly resistant (or “hot”) reactions to globalization, individual-level adaptations remain oriented towards conformity to dominant life expectations, which remain largely unchanged, despite decreasing rewards. However, a socially withdrawn sub-group (the so-called hikikomori) appears to be unable to conform yet is also unwilling to rebel. The experimental evidence we review suggests such youth deviate from typical Japanese motivational patterns but have not necessarily become more Western. This poses serious problems in an interdependence-oriented culture, but the paralysis of this group seems to be an outcome of labor market change rather than a psychopathology. Finally, we also identify a contrasting group – whom we call the quiet mavericks – that adapts in creative and integrative (or "cool") ways by negotiating conformist pressures tactfully. Our account sheds light on just how complex and painful the psychological and sociological effects of globalization can be for young people in conformist societies, with implications to policy and social sustainability.